2017
DOI: 10.1186/s13000-017-0667-7
|View full text |Cite
|
Sign up to set email alerts
|

Complete mimicry: a case of alveolar rhabdomyosarcoma masquerading as acute leukemia

Abstract: BackgroundA small number of rhabdomyosarcoma (RMS) cases involve the bone marrow. A leukemic presentation of RMS has been reported in a few case series, although almost all cases of leukemic RMS are not completely mimicking leukemia. We encountered a case with RMS cell infiltration of the bone marrow that resembled floating hematological cells.Case presentationWe encountered a rare case of a 15-year-old boy with a 2-week history of left femoral pain. Upon admission, he was afebrile with no other symptoms. No a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Burkitt's lymphoma with marrow involvement, especially if there are prominent vacuolizations, as in our case [1,2]. In the literature, all patients presenting with bone marrow involvement were diagnosed with alveolar type RMS [3].…”
Section: Rms Rarely Involves the Bone Marrow Blastic Cells In Rms Rementioning
confidence: 61%
See 1 more Smart Citation
“…Burkitt's lymphoma with marrow involvement, especially if there are prominent vacuolizations, as in our case [1,2]. In the literature, all patients presenting with bone marrow involvement were diagnosed with alveolar type RMS [3].…”
Section: Rms Rarely Involves the Bone Marrow Blastic Cells In Rms Rementioning
confidence: 61%
“…The most common locations are the head/ neck region and genitourinary tract. Leukemic presentation of RMS with diffuse bone marrow involvement and unknown primary mass is very rare [1]. Most of the time it can be misdiagnosed as acute leukemia.…”
Section: To the Editormentioning
confidence: 99%
“…Bone marrow infiltration by ARMS is uncommon; some cases can mimic acute leukemia at presentation and thus mislead the diagnosis. We conducted a PubMed search of similar cases of ARMS with a leukemic presentation, finding 41 cases of mimicry reported in the literature, the oldest reported four decades ago . We added our case and reviewed the data available from these reports on Table .…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a PubMed search of similar cases of ARMS with a leukemic presentation, finding 41 cases of mimicry reported in the literature, the oldest reported four decades ago. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] We added our case and reviewed the data available from these reports on Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…There were no specific clinical criteria for acute leukemia, the bone marrow aspirate was the one who pleaded for acute leukemia. All these studies have shown that the bone marrow infiltration is uncommon, but when it appears can lead to misdiagnosis, delaying or even losing the diagnosis (17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%